ANALISISIS PERSEPSI STRES KERJA TENAGA KESEHATAN DI MASA PANDEMI COVID-19 DI RUMAH SAKIT â€œXâ€ DI SUMATERA SELATAN TAHUN 2021 - Santi Rosalina; Heriziana Heriziana (Universitas Pahlawan, 2022)
The COVID-19 pandemic has had a profound effect on all aspects of society, including mental health and physical health. WHO and public health authorities around the world are acting to control the COVID-19 outbreak. However, this time of crisis creates stress throughout the population. Fear and anxiety about this new disease, plus other factors can influence job stress (WHO, 2021).